Sustained hyperferritinemia in a child with macrophage activation syndrome secondary to systemic juvenile idiopathic arthritis - perforinopathy: case based review - Cakan, Mustafa; Aktay-Ayaz, Nuray; Gemici, Hakan; Annayev, Agageldi; Citak, Agop; Akcay, Arzu; Ozturk, Gulyuz (TURKISH J PEDIATRICS, 2018)
Systemic juvenile idiopathic arthritis is a subtype of juvenile idiopathic arthritis and characterized by arthritis and many systemic features like fever, rash, hepatosplenomegaly, lymphadenopathy and serositis. Macrophage activation syndrome is the most dreadful complication of systemic juvenile idiopathic arthritis and can cause mortality and morbidity if not recognized and treated early and aggressively. Hemophagocytic lymphohistiocytosis (HLH) is characterized by diminished or absent activities of natural killer cells and cytotoxic T lymphocytes leading to cytokine storm and uncontrolled activation of T cells and macrophages. Primary (familial) HLH is a group of autosomal recessive disorders caused by mutations in the perforin and other related genes and distinctive for onset during early infancy and high rate of mortality. Secondary HLH may be caused by infectious, oncologic and rheumatologic disorders. The term Perforinopathy is used to describe cases with classical familial HLH and also for cases with familial HLH gene mutations but not following a classical familial HLH course. Herein we report a case of chronic perforinopathy in which clinical symptoms started with systemic juvenile idiopathic arthritis and severe macrophage activation syndrome that needed plasma exchange and extracorporeal membrane oxygenation during acute period and ongoing interleukin-1 blockage for sustained hyperferritinemia.
Keywords: hyperferritinemia; macrophage activation syndrome; perforin A91V; perforinopathy; systemic juvenile idiopathic arthritis